High Resolution B-Mode Ultrasonography in Evaluation of Atherosclerosis in Patients with Rheumatoid Arthritis (Faridpur Medical College Journal, 2025)
Rheumatoid arthritis is a chronic, systemic, autoimmune inflammatory disorder affecting various tissues and organs like skin, blood vessels, heart, lungs, and muscles. Vasculitis is an important one of the extra-articular manifestations, leading to gradual thickening of intima-media and atherosclerotic arterial disease. This case control study was carried out to compare the intima-media thickening of both the common carotid and femoral artery between rheumatoid and non-rheumatoid arthritis subjects by high resolution B-mode ultrasonography as well as assessing plaque prevalence in the common carotid artery in Rheumatoid arthritis and morphologic evidence of sub-clinical atherosclerosis in RA patients. Total 40 adult patients with rheumatoid arthritis were taken as cases & 20 matched healthy people were taken as controls. Common Carotid artery intima-media thickness was greater in patients than in controls (mean ± SD 0.52 ±0.09 vs 0.37± 0.08mm, p